Human-induced rapid siltation within a macro-tidal bay during past decades - Liu, Yifei; Xia, Xiaoming; Wang, Xinkai; Cai, Tinglu; Zheng, Jun (Frontiers in Marine Science, 2024)
Tidal bay evolution is the result of the comprehensive influence of multiple factors. It is important to analyze the major factor influence to disassemble the comprehensive effects. This study used remote sensing and bathymetric data to investigate anthropogenic activities and geomorphological changes in Puba Bay, China. From 1964 to 2020, the intertidal zone area was reduced by 64.5 % owing to mariculture ponds and coastal reclamation, of which the former accounted for 60.4 % of the total area. This bay has been silting for five decades, manifested by a 61.5 and 88.4 % decrease in the underwater area and volume, respectively, and a considerable decrease in maximum water depth, cross-sectional terrain depth, and width. Anthropogenic activities reduced tidal prism and tidal velocity, increasing flood dominance, and decreasing ebb dominance in the main channel, causing more siltation. Negative and positive feedback mechanisms were observed between anthropogenic activities, intertidal flat seaward expansion, and bay siltation. Mariculture pond influence, being the major factor, are similar to those of coastal reclamation on geomorphological changes. To maintain the water depth and capacity for material exchange in the bay, preliminary suggestions for mariculture pond management are proposed.